Naturalization of Masculinism: How Female Journalist Leaders in Local Media Resist it - Sunarto, Sunarto (UI Scholars Hub, 2020)
The number of male journalists still dominates the media industries, either print or electronic. This phenomenon also happens in local print media. This condition does not give positive opportunities to female journalists to improve their career to a top position in editorial management. This research focuses on female journalists’ experiences as an editorial management staff of a local print media in Semarang. This research has a main objective to describe significances of the female journalists’ experiences. This qualitative descriptive research used a critical constructionism paradigm as a general guidance to the whole research processes with a critical phenomenology research design. A gender structuration theory was used to understand the phenomenon. Research subjects were four female journalists of a local print media in Semarang who were chosen purposively. All subjects were editorial management staff. Data was analyzed by phenomenological procedures. The result showed that a naturalization of masculinism process took place on female journalist in a local media as part of daily professional activities. All female journalists had to absorb masculinism values as media culture such as courageous, independent, responsible, taking risk, leadership and getting perfection in their professional activities as part of their new personal attribute. Although female journalist adopted the masculinism values such as leadership in the editorial management, they applied female journalism values to be resistant to the dominant ideology. It is suggested to develop internal media policy which can be conducive to female journalists to improve naturally in egalitarian organization.